The Influence of Serial Image Media on Interest in Reading in Social Studies Learning for Class IV Students at Culia Elementary School, Doang Island, Doangan Caddi, Pangkep Regency - Nahariah, Nahariah; Rahmawati, Rahmawati; Yunus, Muh (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
The purpose of this research is to determine the effect of applying serial image media on fourth grade students' reading interest in social studies subjects at Culia Pulau Doang Doangan Caddi Elementary School, Pangkep Regency. This research was conducted at Culia Pulau Doang Doangan Caddi Elementary School, Pangkep Regency, which discusses the application of serial image media. on fourth grade students' reading interest in social studies subjects at SD Culia Pulau Doang Doangan Caddi, Pangkep Regency. This research uses quantitative methods of analysis with a descriptive approach. The data collection technique used in this research is by observation, questionnaires and documentation. The results of the research show that (1) the application of image media was carried out well and effectively, (2) the control class's interest in reading in social studies subjects was still lacking because there were many students who were not focused on learning, whereas in the experimental class there was a prominent difference, students were enthusiastic in learning is also active, and (3) there is an influence of the application of serial image media on class IV learning interest in social studies subjects.